Pengaruh Burnout dan Employee Engagement terhadap Intensi Turnover Karyawan Hotel - Dinda Chairiza; Zulkarnain Zulkarnain; Siti Zahreni (Analitika: Jurnal Magister Psikologi UMA, 2018)
Turnover as an actual form of turnover intention is a general phenomena in hospitality business. There are various factors that influence employee turnover intention, such as burnout experienced by employees and employee engagement that employees. The aim of this research is to determine the influence of burnout and employee engagement toward employee turnover intention at X Group Hotel. Multiple analysis result of this research showed that burnout and employee engagement influenced towards employee turnover intention at X Group Hotel. Burnout positively influenced to employee turnover intention and employee engagement negatively influenced to employee turnover intention at X Group Hotel. The implications of this research are expected the company can know that burnout can increase employee turnover intention, whereas employee engagement is needed to reduce employee turnover intention. However, many other things of the variables that can influence employee turnover intention on hospitality company, in particular if it is a family company.